Group theory analysis of phonons in monolayer chromium trihalides and their Janus structures. Issue 46 (21st November 2022) - Liu, Y. C.; Niu, H. B.; Lin, J. B.; Wang, V.
Abstract : The in-plane and out-of-plane A1 modes in the Janus Y3 –Cr2 –X3 monolayer are both infrared and Raman active and may manifest significant magnetic-phonon coupling and magneto-optical effects in their optical spectra. Abstract : A contrastive investigation of the symmetry aspects of phonons in monolayer chromium trihalides and their Janus structures Y3 –Cr2 –X3 (X, Y = F, Cl, Br, I) was presented within group theory. We classified all phonon vibration modes at the Brillouin-zone center ( Γ ) into irreducible representations. The infrared and Raman activity of optic phonons, Raman tensors, and the possible polarization assignments of Raman active phonons are further predicted. We clarify the discrepancy concerning the Raman and infrared activity of optic modes in monolayer CrI3 . It is also found that the Raman and infrared spectra are exclusive for X3 –Cr2 –X3 but coincident for Janus Y3 –Cr2 –X3 . This distinction plays a vital role in optic spectra identification of the Janus Y3 –Cr2 –X3 monolayer from the X3 –Cr2 –X3 monolayer. To demonstrate the origin of phonon chirality and magnetism intuitively, we derive the symmetry-matched phonon eigenfunctions and the corresponding schematic representations of the eigenvectors for both the F3 –Cr2 –I3 and I3 –Cr2 –I3 monolayers. Our analysis indicates that the spin–phonon coupling, the magneto-optical effect of infrared and Raman active phonons, and the phonon chirality could be observed in the Janus Y3 –Cr2 –X3 monolayer more easily than in the X3 –Cr2 –X3 monolayer. Our results thus provide a detailed guiding map for experimental identification and characterization of the Janus Y3 –Cr2 –X3 monolayer.